2023
DOI: 10.1186/s40795-023-00672-6
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast intake and associated factors and barriers among tertiary institution students in the Western Region, Ghana

Abstract: Background Breakfast is considered the day’s most important meal. Skipping breakfast consumption is detrimental to health and intellectual performance. University life has tight schedules and rigorous intellectual activities often very early in the morning. This study aimed at assessing breakfast intake and its associated factors among the students of Takoradi Technical University (TTU). Methods This was a descriptive cross-sectional study. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Students were more likely to consume breakfast daily in 2016, with a decrease of 11% by 2020. Research has previously identified potential barriers to students consuming regular breakfast, including financial insecurity, negative mood, health conditions, limited cooking facilities, weight control, and poor time management skills [29][30][31]. Whilst these barriers exist, the current study only identified the trend that students consume breakfast less than previously, and we did not explore the potential contributing factors concerning why this may be occurring among this population group or worsen over time.…”
Section: Discussionmentioning
confidence: 72%
“…Students were more likely to consume breakfast daily in 2016, with a decrease of 11% by 2020. Research has previously identified potential barriers to students consuming regular breakfast, including financial insecurity, negative mood, health conditions, limited cooking facilities, weight control, and poor time management skills [29][30][31]. Whilst these barriers exist, the current study only identified the trend that students consume breakfast less than previously, and we did not explore the potential contributing factors concerning why this may be occurring among this population group or worsen over time.…”
Section: Discussionmentioning
confidence: 72%
“…This leads to missing breakfast and thus unable to meet nutritional needs. In the long run, it is proven that it will lead to students being inactive in class, poor concentration and poor memory [29]. An interesting finding from this same study is female students are more likely to have regular breakfast as compared to males, who are more likely to skip breakfast [35].…”
Section: Theme 4: Effects On University Studentsmentioning
confidence: 62%
“…In the western region, students who take regular breakfast have better memory, activeness, performance and ability to meet the required nutrient value for their academics. If students become malnourished, they may perform badly in class due to their poor nutritional status leading to poor activeness, memory and general performance in the morning [29]. Based on the study, approximately 36%…”
Section: Theme 4: Effects On University Studentsmentioning
confidence: 97%
See 2 more Smart Citations